Depression, lifestyle factors and cognitive function in people living with HIV and comparable HIV‐negative controls. Issue 4 (8th February 2019) - De Francesco, D; Underwood, J; Bagkeris, E; Boffito, M; Post, FA; Mallon, PWG; Vera, JH; Williams, I; Anderson, J; Johnson, M; Sabin, CA; Winston, A; et al.
Abstract : Objectives: We investigated whether differences in cognitive performance between people living with HIV (PLWH) and comparable HIV‐negative people were mediated or moderated by depressive symptoms and lifestyle factors. Methods: A cross‐sectional study of 637 'older' PLWH aged ≥ 50 years, 340 'younger' PLWH aged < 50 years and 276 demographically matched HIV‐negative controls aged ≥ 50 years enrolled in the Pharmacokinetic and Clinical Observations in People over Fifty (POPPY) study was performed. Cognitive function was assessed using a computerized battery (CogState). Scores were standardized into Z ‐scores [mean = 0; standard deviation (SD) = 1] and averaged to obtain a global Z ‐score. Depressive symptoms were evaluated via the Patient Health Questionnaire (PHQ‐9). Differences between the three groups and the effects of depression, sociodemographic factors and lifestyle factors on cognitive performance were evaluated using median regression. All analyses accounted for age, gender, ethnicity and level of education. Results: After adjustment for sociodemographic factors, older and younger PLWH had poorer overall cognitive scores than older HIV‐negative controls ( P  < 0.001 and P  = 0.006, respectively). Moderate or severe depressive symptoms were more prevalent in both older (27%; P  < 0.001) and younger (21%; P  < 0.001) PLWH compared with controls (8%). Depressive symptoms ( P  < 0.001) and use of hashish ( P  = 0.01) were associated with lower cognitive function; alcohol consumption ( P  = 0.02) was associated with better cognitive scores. After further adjustment for these factors, the difference between older PLWH and HIV‐negative controls was no longer significant ( P  = 0.08), while that between younger PLWH and older HIV‐negative controls remained significant ( P  = 0.01). Conclusions: Poorer cognitive performances in PLWH compared with HIV‐negative individuals were, in part, mediated by the greater prevalence of depressive symptoms and recreational drug use reported by PLWH.